2022
DOI: 10.1007/s00213-022-06106-8
|View full text |Cite
|
Sign up to set email alerts
|

How to account for hallucinations in the interpretation of the antidepressant effects of psychedelics: a translational framework

Abstract: Rationale Recent trials with psychedelics in major depressive disorder and treatment-resistant depression showed remarkable improvements in depressive symptoms that can last for up to several months after even a single administration. The lack of an appropriate placebo control group—as patients are often able to discriminate the subjective effects of the drug—and an incomplete understanding of the role of the hallucinogenic and mystical experience, hampers the interpretation of these therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…The HTR is mostly regarded as a measure of drug-induced hallucinogenic effects [ 28 , 64 ]. However, some argue that although hallucinogens induce HTR, they do not fully represent hallucinatory behavior [ 65 ]. Whether these HTR observed in WD-fed mice correspond to the head bobbing in HE patients, or merely a behavior caused by serotonin changes, should be further evaluated, particularly if previously identified 5-HT receptors are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…The HTR is mostly regarded as a measure of drug-induced hallucinogenic effects [ 28 , 64 ]. However, some argue that although hallucinogens induce HTR, they do not fully represent hallucinatory behavior [ 65 ]. Whether these HTR observed in WD-fed mice correspond to the head bobbing in HE patients, or merely a behavior caused by serotonin changes, should be further evaluated, particularly if previously identified 5-HT receptors are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Here too, an ED 50 dose can be calculated. In effect, the procedure can identify (i) whether or not the test drug produces stimulus 13,62,63 As mentioned above, certain hallucinogenic indolealkylamines such as LSD (8) are structurally similar to the neurotransmitter serotonin (5-HT, 10). Hence, it was initially thought that these agents might act via a serotonergic mechanism.…”
Section: Receptorsmentioning
confidence: 99%
“…183 Ketanserin (initially referred to as R 41 468) and the structurally related pirenperone were identified as the first 5-HT 2 -versus 5-HT 1 -selective antagonists in the early 1980s, 184,185 and Colpaert et al 186 found that pirenperone was a potent antagonist of LSD in rats trained to discriminate LSD from vehicle. Both ketanserin and pirenperone were soon found to very potently antagonize the stimulus effects of DOM, and DOM-stimulus generalization to, for example, mescaline (2), LSD (8), and 5-OMe DMT (9b), suggesting a common stimulus action via activation of 5-HT 2 receptors. 187 Later, the stimulus effect of DOM in monkeys, to which substitution occurred with DOI, R(−)DOM, and LSD, 188 was also blocked with 5-HT 2 antagonists including ketanserin.…”
Section: -Ht 2a Serotonin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a stronger study design should include, apart from an inactive control, an active control condition, such as an effectively psychoactive placebo able to simulate the subjective and acute effects of psilocybin [ 58 ]. Theoretically, an active placebo that mimics psychedelic effects without providing therapeutic benefit might appear appropriate for this purpose, although one would argue that it may well be the “mystical state” itself that may drive the beneficial effects [ 31 , 32 , 82 ]. Finally, some subjects are inclined towards a rational philosophical approach that strongly denies even the mere existence of a “mystical experience”, including its role in the healing process [ 83 , 84 , 85 , 86 ].…”
Section: Challenges Limitations and Suggestionsmentioning
confidence: 99%